Pengaruh Manajemen Keuangan dan Stabilitas Penjualan terhadap Kelangsungan Hidup Usaha pada Perusahaan yang Mengalami Krisis Keuangan - Moh. Tahang; Sukardi Sukardi (Jurnal Manajemen Kreatif dan Inovasi, 2023)
This study aims to analyze the effect of financial management and sales stability on business survival in companies experiencing financial crisis. The research method used is a qualitative approach with case studies on several companies facing financial crises in different industries. Data were collected through in-depth interviews with company executives, analysis of financial statements, and evaluation of implemented management strategies. The research was conducted over a three-month period, starting from January to March 2023. The results show that effective financial management is essential to deal with the financial crisis and affects business survival. Companies that are able to manage financial resources well, restructure debt, and optimize the use of capital will have a greater chance of surviving a crisis. In addition, sales stability is also a crucial factor in the survival of the company. Product diversification, market expansion, and efforts to maintain market share help companies to cope with demand fluctuations and reduce the negative impact of the economic crisis. While this research provides valuable insights, there are limitations in the number of case studies and the focus on qualitative data. The implication of this study is that it is important for companies to strengthen financial management and improve sales stability in an effort to overcome the financial crisis and maintain business viability.